Light conditions and the evolution of the visual system in birds - Fröhlich, Arkadiusz; Ducatez, Simon; Neˇmec, Pavel; Sol, Daniel (Evolution; international journal of organic evolution, 2024)
Despite vision being an essential sense for many animals, the intuitively appealing notion that the visual system has been shaped by environmental light conditions is backed by insufficient evidence. Based on a comprehensive phylogenetic comparative analysis of birds, we investigate if exposure to different light conditions might have triggered evolutionary divergence in the visual system through pressures on light sensitivity, visual acuity, and neural processing capacity. Our analyses suggest that birds that have adopted nocturnal habits evolved eyes with larger corneal diameters and, to a lesser extent, longer axial length than diurnal species. However, we found no evidence that sensing and processing organs were selected together, as observed in diurnal birds. Rather than enlarging the processing centers, we found a tendency among nocturnal species to either reduce or maintain the size of the two main brain centers involved in vision-the optic tectum and the wulst. These results suggest a mosaic pattern of evolution, wherein optimization of the eye optics for efficient light capture in nocturnal species may have compromised visual acuity and central processing capacity.
Keywords: biologická evoluce; focal length; Light; eye shape; colliculus superior; zrak; světlo; Biological Evolution; Birds; light sensitivity; Superior Colliculi; thalamofugal pathway; tectofugal pathway; zvířata; zraková ostrost; fylogeneze; Visual Acuity; eye size; ptáci; Phylogeny; Vision, Ocular; Animals